The Effects of Filtrate of the Secretion of the Cryptomphalus Aspersa on Photoaged Skin - Fabi, Sabrina Guillen; Cohen, Joel L; Peterson, Jennifer D; Kiripolsky, Monika G; Goldman, Mitchel P (Journal of drugs in dermatology, 2013)
Growth factors (GFs) are chemical messengers that regulate specific cellular activities such as cell proliferation and formation of the extracellular matrix. GFs may be derived from a variety of sources, including animals. Evaluate the safety and efficacy of a topical antiphotoaging product containing secretions of the snail Cryptomphalus aspersa (SCA) for the improvement of facial rhytides. This was a 2-center, double-blind, randomized, 14-week study in which 25 patients with moderate to severe facial photodamage were treated with an emulsion (with 8% SCA) and liquid serum (with 40% SCA) on one side of the face and placebo on the contralateral side for 12 weeks. Silicone skin impressions of periocular rhytides were performed at baseline and after 12 weeks of treatment. Patient and physician assessments were also performed at 8, 12, and 14 weeks. Periocular rhytides on the active ingredient side showed significant improvement after 12 weeks (P=.03) and improved texture to a greater degree than placebo at 8 and 12 weeks, as well as 2 weeks after discontinuing the product (14 weeks). Daily application of topical products containing SCA proved effective and well tolerated for improvement in coarse periocular rhytides and fine facial rhytides. Subjects noted a significant degree of improvement in fines lines at the 8-week time point on the SCA-treated side (P≤.05) but did not report a significant difference in the quality of their skin.